Decision-Making Process for Improving The Marketing Strategy of Bakso Benhil Purwokerto Using Integrated SWOT-TOWS AHP Method - Pradana, Mega Dita; Hermawan, Pri (Syntax Corporation, 2025)
Bakso Benhil Purwokerto, a micro, small and medium enterprise (MSME) established in July 2024, faced challenges in achieving sales targets, with a decline in sales in the third month since opening. This research uses SWOT-TOWS and Analytic Hierarchy Process (AHP) methodologies to identify and prioritise strategic solutions to increase revenue and ensure sustainable business growth. The SWOT analysis highlighted strengths such as strategic location in the student culinary area, variety of high-quality meatball products, and halal certification. However, weaknesses such as limited digital promotion and customer knowledge were also found. External opportunities include the trend of digitalisation of MSMEs and the increasing demand for convenience food among students, while threats include fierce competition and fluctuating raw material prices. By integrating these factors in the TOWS matrix, strategy alternatives were formulated and prioritised using the AHP method. The most optimal strategy is to increase digital marketing, including the development of engaging social media content, collaboration with local influencers, as well as promotional programmes on online ordering platforms. This strategy aims to expand market reach, increase brand awareness, and ultimately increase business revenue. This research provides a strategic framework that can be applied by businesses in the food and beverage industry.